Waterproof Light‐Emitting Metal Halide Perovskite–Polymer Composite Microparticles Prepared via Microfluidic Device. (7th March 2021) - Kim, Kyung Hak; Park, Jin Kyoung; Im, Sang Hyuk; Park, Bum Jun
Abstract: Waterproof light‐emitting perovskite–polymer composite microparticles are synthesized by a continuous one‐step microfluidic reactor, which enables in situ production of metal halide perovskite nanoparticles (MHP‐NPs) by the ligand‐assisted reprecipitation process (LARP) and the encapsulation of MHP‐NPs by UV cross‐linking polymerization in the microfluidic channel. Successful encapsulation of MHP‐NPs in polymer microparticles is attributed to the co‐dispersion of an LARP solution and UV polymerizable solution in an aqueous continuous phase within the microfluidic channel, in which N, N ‐dimethylformamide, in co‐dispersion droplets, is continuously extracted to the aqueous medium upon UV polymerization. MHP‐NPs–polymer composite microparticles show enhanced stability against air and moisture. Abstract : Waterproof light‐emitting perovskite (metal halide perovskite nanoparticles (MHP‐NPs))–polystyrene (PS) composite microparticles with a narrow size distribution are fabricated by a continuous one‐step microfluidic method. The obtained MHP‐NPs–PS composite microparticles show extremely enhanced stability against air and moisture, in which the particles are stable in water at least for 21 days and in air at least for 168 days.